Human Capital Management Concepts: Aspect People Development and Organization Development (Study Literature Review) - Murdiono, Jatmiko; Susita, Dewi (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature research is expected to help future authors in determining human resource management research. The research article determining the concept of human resource management: aspects of human resource development and organizational development is a scientific literature article in the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and comes from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Aspects of Human Resource Development affect the Concept of Human Resource Management; and 2) Organizational Development Aspects affect the Concept of Human Resource Management.